PENGARUH TERAPI SPIRITUAL TERHADAP TINGKAT KECEMASAN PASIEN PRE-OPERASI: LITERATURE REVIEW - Ira Lestianti; Gamya Tri Utami; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Surgery is a potential and actual threat to a person's integrity, which can generate an anxiety response in the patient, the patient who is able to control his perception of the operation he is going to undergo, will be able to bring calm to himself, one's calm can be obtained from a spiritual level, one's distance from spiritual can cause a person to stress easily in dealing with problems in his life. The purpose of this literature study is to determine the effect of spiritual healing on the anxiety level of preoperative patients. The method used is literature review. The article search uses Google Scholar and PubMed with the keywords spirituality, anxiety, preoperative patients in the 2016-2020 period. Based on the 7 articles reviewed, it shows that there is an influence between spiritual healing on the level of anxiety in patients who are going for surgery. The high spirituality possessed by a patient can reduce the anxiety experienced by preoperative patients. This is because someone who has spiritual always surrenders to God so that he creates his own calm in facing the operation he will undergo. Spiritual healing interventions can improve emotional intelligence, be able to understand the condition, surrender and realize that everything is a blessing from Allah SWT so that it can increase coping which can reduce anxiety levels. Nurses can provide spiritual intervention in pre-operative patients to reduce anxiety levels. Keywords: Anxiety, preoperative patients, spirituality